Peran Orang Tua Dalam Mengawasi Perkembangan Perilaku Anak Dari Pengaruh Gadget (Media Sosial) - Mariantika, Ni Putu; Suardika, I Kadek (Jayapangus Press, 2021)
Globalization brings significant changes to all aspects of human life. The increasing integration process in all aspects of life encourages increasingly sophisticated developments. Such as the emergence of communication technology, namely gadgets or smartphones. Advances in information technology can already be felt by all levels of world society, one of which is the existence of social media. Social media has a tremendous influence, apart from being a communication tool, social media also acts as an information center. In addition to having a positive impact on human life, in fact the influence of this technological development can have a negative impact if misused. This research uses a type of qualitative research with a literature study. The results of this study indicate that in maintaining the development of children's behavior, parents have an important and main role in supervising, accompanying, and providing understanding to children about the magnitude of the influence of technological developments, especially the use of social media. So that parents must be able to provide understanding to children, so that children can use gadgets wisely and not excessively. The efforts that can be made by parents in monitoring children's development are as follows: (1) Limit children's playing time. (2) Parents can make rules and agree with children. (3) Parents must be able to place themselves in accordance with the times. (4) Give special time and attention to children.